PRINCIPALS’ VIEW ON PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN PEKANBARU, RIAU-INDONESIA - Hadriana Hadriana; Isjoni Isjoni; Mahdum Mahdum; Azhar Azhar (International Journal of Educational Best Practices, 2020)
It cannot be denied that the performance of teachers will greatly influence the success of schools in achieving its goals. This descriptive research is intended to discuss: (1) the principals' view on the performance of public elementary school teachers in Pekanbaru, Riau, Indonesia; (2) principals' expectations for the teachers' performance in the future; and (3) challenges faced by principals to improve teachers' performance in the future. This descriptive quantitative research was carried out at public elementary schools in Pekanbaru in May 2019 to October 2019. By using a proportional random sampling technique, 66 of 191 elementary school principals spread across 12 districts in Pekanbaru were selected as the sample. The questionnaire addressed to the principal was used as an instrument which was then analyzed through descriptive statistical analysis. In the end, it can be concluded that the best performance of teachers is in implementing the learning process. However, their performance in carrying out additional tasks in schools was rated by principals as the lowest average of all categories. The principals' expectations of the teachers' performance in the future are related to improving teacher competencies as well as improving the ability to utilize technology and equipment available at school. While the challenges faced, however, are related to the lack of willingness of teachers to continue their education and limited funds to participate in various training.